Why Islamization of Knowledge? Why the Journal? - al-Alwani, Taha Jaber (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1995)
The Editor-in-Chief, Taha Jaber al-Alwani, discusses the scarcity of journals that address the concept of “Islamization of knowledge,” which came to represent in the past few years a unique Islamic epistemological and methodological approach, and is being discussed as an important intellectual, epistemological, and methodological issue. The study describes important prospects of change in the Muslim world and highlights the purpose of publishing this journal, citing articles by Jamal al-Din al-Afghani published in Al-Manar magazine. The study also explains the development of the concept of “Islamization of Knowledge” throughout the past years, and questions what the Islamic civilizational project has done to revive the Ummah in the past century. The study concludes with explaining the six pillars of “Islamization of Knowledge” methodology.